Managing the future in financial institutions meeting the challenge with better information - Mabberley, Julie (Pearson Education, 1997)
Managing the Future in Financial Institutions shows how activity-based costing techniques can be used to calculate the costs in making your organization's processes more accurate. It gives practical advice on how to use activity based information (ABI) to motivate, measure and manage change effectively.